SAT0134 Patient perceived benefits and side effects of therapeutic interventions in fibromyalgia. (1st June 2001) - Dessein, PH; Stanwix, AE; Moomal, Z
Abstract : Background: The efficacy of treatment programs in fibromyalgia (FM) as currently used in practice is unsatisfactory and more innovative and effective therapies need to be developed. Objectives: The present study comprises part of an audit of a rheumatology clinic in which central sensitisation and neuroendocrine deficiencies were considered in the evaluation and management of FM. Methods: Forty two consecutive female FM (22 primary; 20 sary) patients, who had been followed up for at least 2 months, were enrolled. Their mean (SD, range) age was 42 (12, 15–78), disease duration 8 (11, 0.3–45) and follow up duration 2.9 (2.2, 0.28–8.6) years, respectively. Patients completed Fibromyalgia Impact Questionnaires (FIQ) and reported on the benefits and side effects of each intervention. Results were expressed as mean (SD) where appropriate. Results: The total FIQ improved from 74.1 (11.9) to 21.6 (13.2) (p < 0.001). N users and% patients of users benefiting, experiencing side effects and discontinuing treatment for the different interventions were: (1) dehydroepiandrosterone: 33, 97, 6, 6; (2) IM methylprednisolone (120 mg): 33, 91, 9, 21 (duration of benefit: 2.4 (2.6), range 0–13 months); (3) exercise: 30, 100, 3, 0; (4) diet: 30, 100, 0, 0; (5) NSAID: 26, 69, 31, 50; (6) hydrocortisone: 26, 73, 35, 31; (7) clonazepam: 19, 89, 11, 21; (8) clonidine: 18, 90, 0, 22; (9) tri/tetracyclics: 18, 89, 44, 39; (10) trazodone: 16, 87, 25, 13; (11) subcutaneous sterile water: 16, 87, 0, N/A (duration of benefit: 2.5 (3.1), range 0–12 months); (12) pemoline: 14, 64, 21, 71; (13) fludrocortisone: 13, 85, 8, 38; (14) chloroquine (in secondary fibromyalgia only): 12, 100, 0, 8. More detailed results will be presented. Each FIQ score improved more in secondary as compared to primary FM and these differences reached significance for tiredness and morning tiredness (p < 0.04). After controlling for the use of chloroquine, the respective differences disappeared. Conclusion: Although none of our patients were involved in disability claims and only 4 (10%) were not working because of their disease, our results suggest that an individualised and multimodal management approach is associated with a marked improvement in health status in FM. Also, the potential role of chloroquine in primary FM deserves evaluation. References: Wolfe F, et al . Arthritis Rheum. 1997;40:1571–9 Dessein PH, et al . Pain 2000;86:213–15